Overovanie tesnosti pracovného priestoru motora Kia Cee´D - Bernát, Rastislav; Záležák, Zoltán (Univerzita Pardubice, 2012)
The conservation of the required parameters is focus on a performance, ecology and an economy of internal combustion engines that require periodic compliance inspections as well as implemented of regular maintenance given to the lifetime of the individual components. The assessment operability engine is based on different methods and tests. One of them is detection a gasket of the combustion chamber. Given paper is closely connected with the verification of gasket directly in a combustion engine in the Kia Cee´d. We match the values specified by the manufacturer and then we evaluate the overall condition of the engine. The measuring chain has been designed for achieve these facts as well as design and construction of the adapter needed to connect the measuring device.
Verify of a gasket of working place the engine Kia Cee´d
Keywords: diagnostics; gasket of combustion chamber; engine lifetime